Structural and compensatory trends in spinopelvic parameters of lumbosacral transitional vertebrae: A retrospective cohort analysis - Nikita Das; Ravi Dhamija; Orlando Martinez; John Francis; Rohit Mauria; Collin M. Labak; Eric Z. Herring; Gabriel Smith (World Neurosurgery: X)
Objective: Lumbosacral transitional vertebrae (LSTV) are an underdiagnosed source of low back pain (LBP), or Bertolotti Syndrome. This study identifies trends in radiographic lumbo–pelvic parameters among LSTV patients that may serve as prognostic indicators for surgery. Methods: A retrospective chart review identified LSTV patients using a free-text search of our institution's electronic medical record for terms related to “LSTV” and ''Bertolotti.'' Patients lacking radiographic evidence of abnormal fusion between L5 and the sacrum/ilium were excluded. Clinical features and spinopelvic parameters, including lumbar lordosis (LL), pelvic incidence (PI), and pelvic tilt (PT) were analyzed. Results: Of 122 LSTV patients, 108 (88.5 %) had LBP consistent with Bertolotti Syndrome. Median L4-L5 lordosis was 17.9° [16.9°, 18.9°], L5-S1 lordosis was 15.2° [14.2°, 16.2°]. Median PI was 65.7° [63.4°, 67.9°], with a PI-LL mismatch of 8.4° [6.1°, 10.7°]. Median PT was estimated at 25.1° [23.3°, 26.9°]. Significant associations existed between pain severity and PT > 35° (p = 0.004), as well as increased PI (p = 0.03). Castellvi Type II LSTV patients were more likely to have an L5/S1 angle >15° (p = 0.02). Conclusions: This study aims to improve and understand the impact of spinopelvic parameters for patients with LSTV. Elevated Pelvic Tilt and Pelvic Incidence are associated with increased risk of LSTV manifesting as Bertolotti Syndrome. Additionally, the lumbosacral transition may not be located at L5/S1 in these patients. Development of algorithm-based technologies that identify LSTV radiographically and measure corresponding spinopelvic parameters using standardized protocols may facilitate improvements in care for this patient population.